KETERKAITAN EFEKTIFITAS HUKUMAN DIKAITKAN DENGAN LEMBAGA PEMASYARAKATAN - Bungaran Marulitua; Xikhem Fernady Simanjuntak; Gaby Varera Angeline; Genta Bakas Dwiansa (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2026)
This study examines the relationship between crime, punishment, and the role of correctional institutions (Lapas) in the Indonesian penal system, focusing on the effectiveness of imprisonment and inmate development. The study employed a literature review method with a qualitative descriptive approach and analyzed scientific journals. The results indicate that the success of sentencing is determined not only by the sentence imposed, but also by the quality of guidance within the prison. Prisons play a crucial role in fostering legal awareness, reducing recidivism, and preparing inmates for social reintegration. However, limited capacity, resources, facilities, and supervision hinder the effectiveness of guidance. In conclusion, optimizing the function of prisons through a rehabilitative approach, education, and skills training is key to achieving a humane, just penal system that is capable of reducing recidivism.